2007
DOI: 10.2174/092986707780059625
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumoral Mode of Action of Imiquimod and Other Imidazoquinolines

Abstract: Imiquimod, the lead compound of the imidazoquinoline family of nucleoside analogues, has shown good efficacy against a variety of tumors of different origin. The mode of action of imiquimod and related compounds, which we have begun to understand in some detail in recent years, is complex and interesting inasmuch as it appears to comprise several presumably mutually enhancing components. Predominant amongst its actions is the induction of pro-inflammatory cytokines through agonistic activity towards Toll-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 89 publications
0
54
0
3
Order By: Relevance
“…It is the lead compound of the imidazoquinoline family and has been studied most extensively. Most of the findings concerning the antitumoral mode of action of TLR7/8 agonists, clinical efficacy and safety reviewed here have been obtained with imiquimod (Scho¨n and Scho¨n, 2007). Imiquimod activates preferentially TLR7; its agonistic activity at TLR8 appears to be much weaker (Lee et al, 2003).…”
mentioning
confidence: 94%
“…It is the lead compound of the imidazoquinoline family and has been studied most extensively. Most of the findings concerning the antitumoral mode of action of TLR7/8 agonists, clinical efficacy and safety reviewed here have been obtained with imiquimod (Scho¨n and Scho¨n, 2007). Imiquimod activates preferentially TLR7; its agonistic activity at TLR8 appears to be much weaker (Lee et al, 2003).…”
mentioning
confidence: 94%
“…natural and synthetic agents with antimicrobial and antitumor properties, such as imidazoquinolines and taxanes, have been shown to induce a broad range of cytokines in cell culture and/or in vivo (Burkhart et al, 1994;Schön and Schön, 2007). Furthermore, induction of TNF-␣ by imidazoquinolines has been shown to be mediated through agonist activity toward Toll-like receptor (TLR)-7 and TLR-8 (Schön and Schön, 2007).…”
mentioning
confidence: 99%
“…They induce the activation of nuclear factor-κB, which leads to the transcription of cytokines and chemokines through a myeloid differentiation protein 88-dependent pathway. Topical imiquimod was the first Food and Drug Administration approved drug acting as an agonist of TLR7 (40,41). Several studies reported high efficacy of imiqimod for the treatment of superficial BCC with a cure rate ranging from 43-94% (42-45), whereas it is less efficacious for nodular BCC with a cure rates of 50-65% (43,46).…”
Section: Discussionmentioning
confidence: 99%